Hypersecretory ductal carcinoma cystic infiltrating breast - Martínez, Natalia; Andrade, Eduardo; Centurión, Dardo; Muguruza, Alvaro (Cirugía del Uruguay, 2001)
The cystic hypersecretory carcinoma constitutes a rare variant of mammary duct carcinoma. l t is characterized, both macro - and microscopically - by a marked multicystic secretory image with gelatinoid contents similar to those of thyroid colloid, as we/1 as a carcinomatous micropapillary coating over adjacent cysts and ducts. The majority of cases published involve intraduct carcinomas with diameters as large as 1 O cms. The patient, a 43 year-old woman, consulted with respect to a palpable tumoration in left breast. Mammography showed an image which was compatible with that of a phy/lode cystosarcoma; the possibility of its being a malignant lesion was not to be discarded. Quadrantectomy, supplemented by e x temporaneous study, was not conclusive. Anatomopathologíc examination of cross sections in paraffin proved it to be an l nfiltrating C ystic Hypersecretory Duct Carcinoma. Subsequent axillary dissection was marked by the absence of metastases in lymph nodes.